EUROPEAN AND INTERNATIONAL STANDARDS IN THE FIELD OF HUMAN TRAFFICKING - Valvo, Anna Lucia (NBP. Nauka, bezbednosti, policija, 2017)
Trafficking in human beings is a phenomenon which from time immemorial the international community has to face through the arrangement of legal instruments for its prevention and suppression. The first international Conventions that faced the problem dates back to the early ’900 although, at the time, trafficking in human beings was better known as "white slave trade" and concerned a phenomenon smaller than today. In fact, today’s trafficking in human beings has boundaries wider than in the past, not only in terms of quantity but also in terms of the quality of the organized criminal groups who are engaged in human trafficking. Qualified as a crime against humanity by the Rome Statute of July 1998 establishing the International Criminal Court, which in its art. 7 includes enslavement as a crime against humanity prohibited by the Universal Declaration of Human Rights of December 10, 1948, today trafficking in human beings is also expressly prohibited by the Charter of Fundamental Rights of the European Union which in its art. 5 provides that “no one shall be held in slavery or servitude; no one shall be required to perform forced or compulsory labour; trafficking in human beings is prohibited”.